Kindergartners' Spontaneous Focus on Number During Picture Book Reading - Sanne Rathé; Joke Torbeyns; Bert De Smedt; Minna M. Hannula-Sormunen; Lieven Verschaffel (Springer, 2022)
Children's Spontaneous Focusing On Numerosity (SFON) predicts later mathematics performance. This association is assumed to rely on children's self-initiated practice in number recognition during everyday activities, which would enhance their further mathematical development. Consequently, SFON in experimental tasks should be associated with SFON during everyday activities. The present contribution aims to enhance our understanding of this association by critically discussing the major results of two recently conducted studies on the association between SFON in experimental tasks and SFON during picture book reading. Study 1 revealed no association between children's SFON in an Imitation task and their number-related utterances during numerical picture book reading. Study 2, in which we contrasted two different SFON tasks and their association to picture book reading, revealed a positive association between children's SFON in the Picture task (but not in the Imitation task) and their number-related utterances during picture book reading. Theoretical, methodological, and educational implications are discussed.
Contemporary Research and Perspectives on Early Childhood Mathematics Education